Aqueous-Phase Adsorption Of Phenolic Compounds On Activated Carbon. - Maarof, Hawaiah Imam; Hameed, Bassim H.; Ahmad, Abdul Latif (2003)
Laboratory batch studies were conducted on adsorption of phenol, 3-chlorophenol and o-cresol from aqueous solution by Norit Granular Activated Carbon (NAC 1240).